Vibration and Long-Term Performance Analysis of Pile-Plank-Supported Low Subgrade of Ballastless Track under Excitation Loads - Junjie Huang; Qian Su; Ting Liu; Xun Wang (Shock and Vibration)
Pile-plank structures are widely applied for high-speed railway built in soft ground in China. It can be used as a reinforcement to improve the behavior of subgrade by providing vertical confinement to increase their stiffness and strength and reduce the subgrade settlement of ballastless track. However, the use of pile-board structure for soft ground reinforcement of high-speed railway is hindered by the existing gap between applications and theories. To verify vibration characteristics and long-term performance of pile-plank-supported low subgrade of ballastless track and the benefit of pile-board structure, an experimental study was conducted on low subgrade of pile-board under excitation loads using both in situ frequency sweeping and cyclic loading experiments. The frequency sweeping experimental results show that the pile-plank-supported low subgrade has smooth stiffness along the longitudinal subgrade and can effectively control the progressive effects of train speed on dynamic stiffness of the subgrade, which ensures driving safety and comfort. The cycle loading experimental results show that the pile-plank-supported low subgrade has favorable long-term dynamic stability, and its dynamic response is uniform along the longitudinal subgrade.